Perfecting of the crawl in non-skilled swimmers: Comparison between the drag reduction and improvement of the propulsion - Invernizzi, P. L.; Scurati, R.; Michielon, G.; Pizzini, G. (Biomechanics and Medicine in Swimming X, 2006)
Swimming results as a compromise between propulsive actions and gliding through water. This research observed the improvements in non-skilled swimmers taught by two specific training programs. The first aimed to have a drag reduction and a better glide (improving the balance, the position in the water and the breath control). The second program aimed to improve the efficiency of the propulsive actions (with respect to continuity and length of the armstroke, rhythm of the actions). The two perfection methods were proposed to 97 non skilled subjects. In the pre-post analysis within each group an improvement of the efficiency index in all male subjects and in the females working on propulsion were found. Moreover and an improvement of long distance swim was recorded in all subjects.